Wage dynamics and promotions inside and between firms - António Dias da Silva; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2006)
We focus on the dynamic relation between wage increases, promotions and job changes. We relate our empirical analyses to the theoretical model of Gibbons and Waldman (1999). In the empirical analyses we use the Portuguese matched employer-employee data Quadros de Pessoal. We conclude from finding significant serial correlation in wage increases and promotion rates that employer learning about the worker's ability might be important. Furthermore, we find that the Portuguese labor market is not competitive. Finally, we argue that employer-reported promotion relate to a large extent to wage increases rather than changes in job tasks and complexity.
urn:nbn:de:101:1-20090622413
Keywords: 330